Clinico-Morphological Pattern of Breast Cancer at In patient Department of Dhaka Medical College Hospital Study of 60 Cases (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Breast cancer incidence is increasing in Bangladesh with changing lifestyles, demographic and socioeconomic profiles. But there is no structured data on clinico-morphological pattern of breast cancer in Bangladesh. Understanding the clinical & morphological pattern of breast cancer of this country will help in early detection & prompt treatment of the cancer.Objective: To find out the clinical features of breast cancer & their morphological pattern at a tertiary level hospital.Methods: This is a cross sectional study. Data were collected prospectively from 60 new female patients with diagnosed breast carcinoma admitted to Dhaka Medical College Hospital at different surgical wards over a period of six months starting from 1st August 2010 to 28th February 2011 with the help of pre-designed semi-structured data collection form for clinical & histopathological data. Male patients, severely ill patients and patients unwilling to take part in the study were excluded. Informed written consent was taken from each case. After analysis & compilation the results were presented in tables, graphs and charts.Results: The mean age of breast cancer patients was 37.13 years. The average duration of symptoms of breast cancer patients before first presentation at tertiary level health facilities was 8.9 months. Most of the patients presented to tertiary level health facilities from 6 to 12 months after appearance of first symptom. Painless lump was the commonest presenting complaint with 43 cases, followed by nipple retraction in 24 cases, peu-de-orange in 21 cases, painful lump in 17 cases, ulceration in 12 cases and nipple discharge in 5 cases. 67% had tumor in the left breast whereas 28% had tumor in the right breast. Only 5% cases presented with bilateral involvement. The most frequent location of primary tumor was upper outer quadrant which is 32 cases followed by central in 9 cases, lower outer in 8 cases, lower inner in 6 cases, upper inner in 3 cases and overlapping lesions in 2 cases. Majority of the patient (69%) presented with a tumor size of more than 5 cm whereas only 3.3% patients presented with tumor size of less than or equal to 2 cm. Axillary lymph nodes were involved in most of the cases(86.66%). Infiltrating ductal carcinoma, NOS (which is an abbreviation for nothing otherwise specified) was the commonest (98.33%) histopathological variant. Most of the patients of this series, i.e. 35 patients had poorly differentiated tumor. 4 patients had well differentiated tumor and 21 patients had moderately differentiated tumor.Conclusion: In my study breast cancer is found to be common among relatively younger age group, majority below 40 years. The patients of breast cancer are coming to a tertiary level hospital very late, mostly with clinical features of advanced disease. For better understanding a series of multi centre studies are neededJ Shaheed Suhrawardy Med Coll, December 2015, Vol.7(2); 49-53